2012
DOI: 10.1101/gad.177774.111
|View full text |Cite
|
Sign up to set email alerts
|

Intronic miR-26b controls neuronal differentiation by repressing its host transcript,ctdsp2

Abstract: Differentiation of neural stem cells (NSCs) to neurons requires the activation of genes controlled by the repressor element 1 (RE1) silencing transcription factor (REST)/neuron-restrictive silencer factor (NRSF) protein complex. Important components of REST/NRSF are phosphatases (termed RNA polymerase II C-terminal domain small phosphatases [CTDSPs]) that inhibit RNA polymerase II and suppress neuronal gene expression in NSCs. Activation of genes controlled by CTDSPs is required for neurogenesis, but how this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 35 publications
3
109
2
2
Order By: Relevance
“…Many studies have demonstrated that miRNAs can function as oncogenes or tumor suppressors, and are often dysregulated in tumors (31). miRNAs play a vital role in many crucial cellular processes, including apoptosis, differentiation, invasion, and proliferation (32)(33)(34). The abnormal expression of miRNA has been reported in many cancers, including breast (35), gastric (36), colorectal (37), and liver cancers (38), as well as leukemia (39) and lymphoma (40).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that miRNAs can function as oncogenes or tumor suppressors, and are often dysregulated in tumors (31). miRNAs play a vital role in many crucial cellular processes, including apoptosis, differentiation, invasion, and proliferation (32)(33)(34). The abnormal expression of miRNA has been reported in many cancers, including breast (35), gastric (36), colorectal (37), and liver cancers (38), as well as leukemia (39) and lymphoma (40).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kloting et al (14) isolated miRNA from different fat depots of overweight and obese individuals in 2009 and Zhao et al (22) profiled 220 miRNAs in pancreatic islets, adipose tissue and liver isolated from diabetes-resistant (B6) and diabetes-susceptible (BTBR) mice. miR-26b is an intronic miRNA located in the intron of the CTDSP1 gene, which is able to regulate its host transcript (23). Emerging evidence has indicated that miR-26b is associated with the development of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was determined that miR-34a is involved in NSC differentiation; miR-34a promotes Notch signaling by repressing Numbl, a negative regulator of Notch signaling that inhibits neuronal differentiation [110] . Additionally, miR-26b activates neurogenesis by suppressing Ctdsp2 protein expression [111,112] . By targeting Nestin, miR-125b promotes NSPC differentiation and migration while inhibiting NSPC proliferation [113] (Figure 2).…”
Section: Neuronal Differentiationmentioning
confidence: 99%